Adapting speaking tasks in English 10 (The Old Version) for the minority students at Yenbai Ethnic Boarding High school - Nguyễn, Thị Ngọc Hà (ĐHNN, 2017)
Description of the students and the teachers of English in Yen Bai Ethnic Boarding High School. Questionaires and interviews for teachers and students. Some suggested techniques of adapting speaking tasks to encourage communication to the 10th grade ethnic students in Yen Bai Ethnic Boarding High School.